Management of Effluent from shrimp farms : the role of sedimentation pond - Soon, Yit Leng. (2001)
The objective of this study was to determine the role of sedimentation ponds in the treatment of effluent from tiger shrimp (penaeus monodon) ponds in Kuching, Sarawak. Effluents discharged from culture ponds during shrimp harvest were analysed at every interval of 10 cm of decrease in pond water level. Water samples were also taken from the sedimentation ponds after the completion of harvest to monitor the changes in the efflient quality through time.